PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V PADA PEMBELAJARAN IPAS DI SDN 134/IV KOTA JAMBI - Kania Salsabila; Asrial; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using the Problem Based Learning model on students' critical thinking skills in science learning for grade V at SDN 134/IV Jambi City. This research was conducted at SDN 134/IV Jambi City in the 2024/2025 school year. This study uses a quantitative approach with the Quasi Experimental Design type. The design used in this study is nonequivalent control group design, where there are experimental groups and control groups. Data collection techniques were obtained by giving essay questions to students. The results of the study showed that there was a significant difference in the average final learning outcomes of the experimental and control groups. This is indicated by the calculation of the t-test with a t count of 7.157> t table 2.004. Thus, Ha is accepted and Ho is rejected. It can be concluded that there is an effect of using the Problem Based Learning model on students' critical thinking skills in science learning for grade V at SDN 134/IV Jambi City